“IN VIVO” ¹H NMR RELAXOMETRY MAPS OF WOMEN NORMAL AND CANCEROUS PELVIS - MORAR, I. A.; PINTICAN, R.; DAVID, R. E.; KOVACS, T.; FECHETE, R. (Studia Universitatis Babeș-Bolyai Physica, 2019)
Transverse relaxation time (T2) and 1H spin density ( ) parameter maps were obtained for the pelvis of two women. For that, two anatomical magnetic resonance (MR) images were recorded in axial orientation with a low echo time (TE1 @ 30 ms) and a large echo time (TE @ 200 ms) for a volunteer with normal pelvis and a patient with endometrial cancer. The largest –value was obtained for the right pelvic bones of patient with endometrial cancer and the lowest one was obtained for the uterus of volunteer with normal pelvis.